The Jogja Library Center Tour: Literacy-Based Inquiry Model to Improve Historical Thinking Skill - Roro Wilis; Dyah Kumalasari (Jurnal Pedagogi dan Pembelajaran, 2025)
A pedagogical approach dominated by a single narrative often neglects the analysis of sources, context, and causal relationships in history. This weakens students' historical literacy skills, thereby affecting their ability to develop practical historical thinking skills. The purpose of this study is to analyze the implementation of the Jogja Library Center Tour inquiry model in history learning, which utilizes old daily newspapers to improve historical Literacy and its implications for improving historical thinking skills. This study used a qualitative method with a case study approach. The subjects were the Deputy Head of the Library Center. The school curriculum field consisted of one person, a history teacher, and three representatives from class XII students. Data were collected through observation, interviews, and document analysis, utilizing the Miles and Huberman interactive model analysis technique. Data were analyzed using Miles and Huberman's interactive analysis model, which includes the stages of data reduction, data presentation, and conclusion. The primary instruments utilized included in-depth interview guidelines, participatory observation guides, and document analysis protocols. The findings show that the Jogja Library Center Tour model significantly enhances students’ historical literacy and historical thinking skills. This inquiry-based literacy model effectively utilizes authentic sources and contextual learning environments and has strong potential for replication to support the Merdeka Curriculum and the School Literacy Movement.